Population dynamics of sorrah sharks (Carcharhinus sorrah) caught in fishery management areas (WPP 711) - Hadinata, Fitra Wira; Yennie, Yennie; Adijaya, Mardan; Neksidin, Neksidin; Wahyudi, Adi Imam; Armos, Nikanor Hersal; Runtu, Kezia Gloria Apriliana (Acta Aquatica: Aquatic Sciences Journal, 2025)
Sorrah shark (Carharhinus sorrah) is one of the catch types that is landed at the Nusantara Pemangkat Fishing Port.  This research was conducted to determine the dynamics of the sorrah shark population caught in the WPP 711 fishery management area. This research was carried out from August to October 2023 at TPI, precisely at the Nusantara Pemangkat Fishing Port, Pemangkat District, Sambas Regency, West Kalimantan.  The method used in this research is a survey. This research used primary and secondary data.  The data collected includes the number of catches (kg), total catch (tails), total length of sharks, weight of sharks and gender.  The ship sampling used purposive sampling and 10% random sampling method.  A total of 152 sharks were landed, consisting of 89 male sharks and 63 female sharks.  With a length range of male sharks 56-79 cm with female sharks 57-74 cm long.  The results of the shark length and weight relationship test showed that the growth pattern of the sorrah shark was negative allometric and had an unbalanced male: female sex ratio of 1.4: 1.Keywords: Allometric; Catch; Long Size; Sex Ratio; Sorrah shark